Perturbation of Stochastic Boussinesq Equations with Multiplicative White Noise - Chunde Yang; Xin Zhao (Discrete Dynamics in Nature and Society)
This paper studies the Boussinesq equations perturbed by multiplicative white noise and shows the existence and uniqueness of the global solution. It also gets some regularity results for the unique solution.